Carbon footprint report 2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
In 2011 CCAFS Coordinating Unit (CCAFS CU) initiated a carbon footprint plan including emission reduction targets and offsetting.